Nieprzekładalność Janowego Prologu? (J 1,1-18) - Górka, Bogusław (Vox Patrum, 2008)
The present paper is focused on translation studies. We analyze to what degree the Prologue of the Gospel of John is translatable into selected Polish translations, and to what degree it can be retranslated into Hebrew. What is new in our approach is the analysis of the inaccuracy of translation of the original text which is apparent in the prototype translation (Ur-translation) of the Vulgate by Jerome. Thanks to the comparison between the Vulgate and Polish translations of the Prologue, and their retranslation into Hebrew, we concluded that they repeat the mistakes of the Vulgate almost automati- cally. When we liberate ourselves from the influence of the Vulgate, we face with yet another difficulty. The Prologue is a text of initiation, and it is translatable according to the dynamie equivalence only for a reader, who was intended by the author of the Gospel of John. For other readers, the Prologue can be translated, morę or less accurately, according to the formal equivalence.